Analisis Kinerja Keuangan Desa Dengan Menggunakan Rasio Keuangan Pada Desa Ranoramba Kecamatan Ende Kabupaten Ende Tahun 2021-2023 - Ismail, Nuraini; Reo, Hermanus (Jurnal Mirai Management, 2024)
The purpose of this research is to analyze the financial performance of Ranoramba Village, Ende District, and Ende Regency for the years 2021-2023 based on the independence ratio, effectiveness ratio, efficiency ratio, and growth ratio. The sample in this study is the realization report of the village budget of Ranoramba for the years 2021-2023. The data analysis used in this study is quantitative descriptive. The research results show that the financial performance of Ranoramba Village in 2021-2023, based on the independence ratio, is classified as very low; based on the effectiveness ratio, it falls into the ineffective category; based on the efficiency ratio, it is categorized as inefficient; and based on the original village income growth ratio, there is a significant increase in original village income, categorized as high.